NADPH- and NADH-dependent metabolism of and DNA adduct formation by benzo[a]pyrene catalyzed with rat hepatic microsomes and cytochrome P450 1A1 - Stiborová, Marie; Indra, Radek; Moserová, Michaela; Šulc, Miroslav; Hodek, Petr; Frei, Eva; Schmeiser, Heinz H; Arlt, Volker M (Monatshefte fur chemie, 2016)
ABSTRACT: Benzo[a]pyrene (BaP) is a human carcinogen that covalently binds to DNA after metabolic activation by cytochrome P450 (CYP) enzymes. Here we investigated the efficiencies of rat hepatic microsomes and rat recombinant CYP1A1 expressed with its reductase, NADPH:CYP oxidoreductase (POR), NADH:cytochrome b5 reductase, epoxide hydrolase and/or cytochrome b5 in Supersomes™ to metabolize this carcinogen. We also studied the effectiveness of coenzymes of two of the microsomal reductases, NADPH as a coenzyme of POR, and NADH as a coenzyme of NADH:cytochrome b5 reductase, to mediate BaP metabolism in these systems. Up to eight BaP metabolites and two DNA adducts were generated by the systems, both in the presence of NADPH and NADH. Among BaP metabolites, BaP-9,10-dihydrodiol, BaP-4,5-dihydrodiol, BaP-7,8-dihydrodiol, BaP-1,6-dione, BaP-3,6-dione, BaP-9-ol, BaP-3-ol, and a metabolite of unknown structure were formed by hepatic microsomes and rat CYP1A1. One of two DNA adducts formed by examined enzymatic systems (rat hepatic microsomes and rat CYP1A1) was characterized to be 10-(deoxyguanosin-N2-yl)-7,8,9-trihydroxy-7,8,9,10-tetrahydrobenzo[a]pyrene (dG-N2-BPDE), while another adduct has similar chromatographic properties on polyethylaneimine-cellulose thin layer chromatography to a guanine adduct derived from reaction with 9-hydroxy-BaP-4,5-oxide. In the presence of either of the reductase cofactors tested, NADPH or NADH, cytochrome b5 stimulated CYP1A1-mediated formation of both BaP-DNA adducts. The results demonstrate that NADH can act as a sole electron donor for both the first and the second reduction of CYP1A1 during its reaction cycle catalyzing oxidation of BaP, and suggest that the NADH:cytochrome b5 reductase as the NADH-dependent reductase might substitute POR in this enzymatic system.
Keywords: Coenzymes; High-pressure liquid chromatography; Enzymes; DNA